Governing global land deals : the role of the state in the rush for land - Wolford, Wendy; Borras, Saturnino M.; Hall, Ruth (Professor); Scoones, Ian; White, Benjamin (Chichester, West Sussex, United Kingdom : Wiley, 2013)
This collection of essays inGoverning Global Land Dealsprovides new empirical and theoretical analyses of the relationships between global land grabs and processes of government and governance.Reframes debates on global land grabs by focusing on the relationship between large-scale land deals and processes of governanceOffers new theoretical insights into the different forms and effects of global land acquisitionsIlluminates both the micro-processes of transaction and expropriation, as well as the broader structural forces at play in global land dealsProvidesnew empirical data on the different actors involved in contemporary land deals occurring across the globe and focuses on the specific institutional, political, and economic contexts in which they are acting.
Governing global land deals : the role of the state in the rush for land / Wendy Wolford, Saturnino M. Borras Jr., Ruth Hall, Ian Scoones and Ben White -- State involvement, land grabbing and counter-insurgency in colombia / Jacobo Grajales -- Road mapping : megaprojects and land grabs in the northern guatemalan lowlands / Liza Grandia -- Land regularization in brazil and the global land grab / Gustavo de L.T. Oliveira -- Negotiating environmental sovereignty in costa rica / Dana J. Graef -- Building the politics machine : tools for'resolving' the global land grab / Michael B. Dwyer -- Indirect dispossession : domestic power imbalances and foreign access to land in mozambique / Madeleine Fairbairn -- Competition over authority and access : international land deals in madagascar / Perrine Burnod, Mathilde Gingembre and Rivo Andrianirina Ratsialonana -- Regimes of dispossession : from steel towns to special economic zones / Michael Levien -- The political construction of wasteland : governmentality, land acquisition and social inequality in south india / Jennifer Baka -- Chinese land-based interventions in senegal / Lila Buckley -- Identity, territory and land conflict in brazil / LaShandra Sullivan.
Originally published as volume 44, issue 2 of Development and Change.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Land use -- Law and legislation -- Developing countries; Eminent domain -- Developing countries; Law and economic development; LAW -- Military; Eminent domain; Land use -- Law and legislation; Law and economic development; Landnahme; Agrobusiness; Lebensmittelindustrie; Regierung; Politik; Developing countries; Electronic books